2009
DOI: 10.1159/000199432
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Pulse Wave Velocity and Fluid Distribution in Hemodialysis Patients

Abstract: Background: In this study, we focused on whether volume overload plays a role in the development of arterial stiffness. Methods: Seventy-three prevalent hemodialysis patients were enrolled in a cross-sectional study. Arterial stiffness was assessed by carotid-femoral pulse wave velocity (PWV), and volume overload was assessed by bioimpedance analysis. Results: Patients were divided into a high PWV group and a low PWV group based on the median of PWV. Age, systolic blood pressure, pulse pressure (PP), extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…It has been shown that excess fluid plays an important role in the development of arterial stiffness in dialysis patients by increasing arterial distension and systolic blood pressure. 47,48 A positive strong correlation has been determined between PWV and excess fluid in our study, suggesting that excess fluid leads to an increase of arterial stiffness and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that excess fluid plays an important role in the development of arterial stiffness in dialysis patients by increasing arterial distension and systolic blood pressure. 47,48 A positive strong correlation has been determined between PWV and excess fluid in our study, suggesting that excess fluid leads to an increase of arterial stiffness and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 71%
“…This finding may be associated with cardiovascular instability and probably increased ECV and BP observed mainly in patients on HD than those on HDF, but because of the good status of the enrolled patients, we did not observe significant differences. A previous study has reported that volume overload plays an important role in the development of arterial stiffness in HD patients [28]. Additionally, it has been reported that PWV varies during dialysis due to alterations in hydration status [29].…”
Section: Discussionmentioning
confidence: 99%
“…This was proven by the loss in body weight in the study group. A lower volume overload should therefore decrease the degree of arterial stiffness [21], which in turn should cause the oscillometric BP measurements to be more accurate.…”
Section: Discussionmentioning
confidence: 99%